A Novel Flavonol-based Fluorescent Probe for Detecting GSH Exhaustion in Polystyrene Microplastic-Induced Liver Injury - Yuzhi Li; Hang You; Jianwei Cui; Qiao Wei; Yurong Wang; Gang Wang; Tao Sun; Zhixing Cao; Yuyu Fang; Yong Wu (Environmental Pollution, 2026)

Comparative Analysis of Sensory Quality and Microbial Communities Between Medium–High- and High-Temperature Daqu From Shangqiu Region - Mengjun Cui; Yurong Wang; Jixiang Sun; Jun Zhang; Haibao Fan; Yanju Li; Zhuang Guo; Huijun Zhao (Current Microbiology, 2026)

Microcystin-LR-induced phosphorylation imbalance and organelle stress: An integrative review of autophagy dysregulation and cross-species toxicity - Zhuoran Teng; Asif Shahzad; Zhe Xu; Jiaojiao Xia; Jinshan Zhang; Yueli Ni; Wenjing Liu; Kun Cui; Yongping Li; Yurong Dong; Ziyuan Bai; Peng Zhang; et al. (Journal of Hazardous Materials, 2026)

Amplifying self-protective room-temperature phosphorescence in carbon dots via electronic-state engineering - Jiahui Tan; Lin Cui; Jian Lei; Jiayi Chen; Yurong Wei; Zhigang Ren; Jie Wang (Chemical Engineering Journal, 2026)

In-Depth Water Quality Analysis in Fengle Reservoir, China - Ran Chen; Jiamin Chai; Zhixu Kang; Yan Li; Lili Dong; Liping Qian; Yurong Wei; Xintong Li; Qidi Liu; Yixin Ma; Jun Cui; Shunli Wan; et al. (Water Conservation Science and Engineering, 2026)

Simple methods for imperfection sensitivity analysis of caisson skirts under suction installation - Ruizhe Xu; Yurong Zhang; Dengfeng Fu; Yue Yan; Wentao Cui; Shuntao Fan; Dong Wang (Computers and Geotechnics, 2026)

Spatial and temporal evolution of wetland ecological quality in the Yellow River Delta: a comprehensive analysis based on multi-temporal remote sensing and improved ecological indices - Ruifeng Liu; Lansong Lv; Yurong Cui; Wenxin Pan; Xiulong Zhang; Juan Fu (Advances in Space Research, 2026)

Regulatory mechanisms of carboxylic ligands with varying carboxyl group richness in Fe(II)-catalyzed ferrihydrite transformation - Yuefei Ding; Anxu Sheng; Jiahao Chen; Yurong Deng; Xinglan Cui; Juan Liu (Geochimica et Cosmochimica Acta, 2025)

High-temperature Daqu of different colors from the Zibo region of China: Analysis of microbial community structure, physicochemical characteristics, and enzymatic activities - Mengjun Cui; Qiangchuan Hou; Yurong Wang; Xinhe Zhao; Chunhui Xin; Ling Xu; Zhuang Guo (World Journal of Microbiology and Biotechnology, 2025)

Characterization and Correlation Analysis of Bacterial Composition and Physicochemical Quality in High- and Medium-Temperature Daqu from China’s Binzhou Region - Mengjun Cui; Wenchao Cai; Peirong Yu; Wei Chen; Chunhui Shan; Guo Zhuang; Yurong Wang (Current Microbiology, 2025)

Simultaneous detection of mixed colorants adulterated in black tea based on various morphological SERS sensors - Qingqing Cui; Jingfei Shen; Huiyan Jia; Tiehan Li; Shuci Cao; Shuai Dong; Yuming Wei; Li Zou; Yurong Chen; Yujie Wang; Jingming Ning; Luqing Li (Food Research International, 2025)

A critical review of biochar for the remediation of PFAS-contaminated soil and water - Dezhan Liang; Caibin Li; Hanbo Chen; Erlend Sørmo; Gerard Cornelissen; Yurong Gao; Febelyn Reguyal; Ajit Sarmah; Jim Ippolito; Claudia Kammann; Fangbai Li; Yerbolat Sailaukhanuly; et al. (Science of The Total Environment, 2024)

Rapid fluorescence detection of black tea fermentation degree based on cobalt ion mediated carbon quantum dots - Shuci Cao; Shuai Dong; Yurong Chen; Jingfei Shen; Qingqing Cui; Changying Sun; Jingming Ning; Luqing Li (Food Control, 2024)

Automatic identification of cirques based on RetinaNet model and pseudo-color image fusion method - Zhenxin Shi; Guiquan Mo; Yurong Cui; Libo Yan; Yunshan Lu; Lina Hou; Lansong Lv; Huixuan Li (Advances in Space Research, 2024)

Spatiotemporal changes of urban heat island effect relative to land surface temperature: a case study of Jinan City, China - Guiquan Mo; Libo Yan; Zhiyong Li; Zongyao Wang; Sixuan Chen; Huixuan Li; Shuwei Zheng; Yurong Cui (Environmental Science and Pollution Research, 2024)

Differential response of Hg-methylating and MeHg-demethylating microbiomes to dissolved organic matter components in eutrophic lake water - Zhengyu Wu; Zhike Li; Bo Shao; Ji Chen; Xiaomei Cui; Xiaoyu Cui; Xianhua Liu; Ying Xin Zhao; Qiang Pu; Jiang Liu; Wei He; Yiwen Liu; et al. (Journal of Hazardous Materials, 2024)

Spatiotemporal patterns of net regional productivity and its causes throughout Ordos, China - Yurong Zheng; Shouhang Du; Wenbin Sun; Cui Feng; Qing Su (Environmental Science and Pollution Research, 2024)

Deciphering microbiomes dozens of meters under our feet and their edaphoclimatic and spatial drivers - Haoran He; Jingxiong Zhou; Yunqiang Wang; Shuo Jiao; Xun Qian; Yurong Liu; Ji Liu; Ji Chen; Manuel Delgado‐Baquerizo; Albert C. Brangarí; Li Chen; Yongxing Cui; et al. (Global Change Biology, 2024)
Microbes inhabiting deep soil layers are known to be different from their counterpart in topsoil yet remain under investigation in terms of their structure, function, and how their diversity is shaped. The microbiome of deep soils (>1 m) is expected to be relatively stable and highly independent from climatic conditions. Much less is known, however, on how these microbial communities vary along climate gradients. Here, we used amplicon sequencing to investigate bacteria, archaea, and fungi along fifteen 18‐m depth profiles at 20–50‐cm intervals across contrasting aridity conditions in semi‐arid forest ecosystems of China's Loess Plateau. Our results showed that bacterial and fungal α diversity and bacterial and archaeal community similarity declined dramatically in topsoil and remained relatively stable in deep soil. Nevertheless, deep soil microbiome still showed the functional potential of N cycling, plant‐derived organic matter degradation, resource exchange, and water coordination. The deep soil microbiome had closer taxa–taxa and bacteria–fungi associations and more influence of dispersal limitation than topsoil microbiome. Geographic distance was more influential in deep soil bacteria and archaea than in topsoil. We further showed that aridity was negatively correlated with deep‐soil archaeal and fungal richness, archaeal community similarity, relative abundance of plant saprotroph, and bacteria–fungi associations, but increased the relative abundance of aerobic ammonia oxidation, manganese oxidation, and arbuscular mycorrhizal in the deep soils. Root depth, complexity, soil volumetric moisture, and clay play bridging roles in the indirect effects of aridity on microbes in deep soils. Our work indicates that, even microbial communities and nutrient cycling in deep soil are susceptible to changes in water availability, with consequences for understanding the sustainability of dryland ecosystems and the whole‐soil in response to aridification. Moreover, we propose that neglecting soil depth may underestimate the role of soil moisture in dryland ecosystems under future climate scenarios.

Spatiotemporal changes of aerosol optical depth and its response to urbanization: a case study of Jinan City, China, 2009–2018 - Zeyu Zhang; Jun Zhou; Jingzhe Liu; Xiaoqian Liu; Yanwen Zhu; Huixuan Li; Yurong Cui (Environmental Science and Pollution Research, 2023)

Fire resistance evaluation of laminated bamboo lumber column under eccentric compression - Zhaoyan Cui; Ming Xu; Ang Li; Liuhui Tu; Jia Zhu; Yurong Shen (Engineering Structures, 2023)

Barley β-glucan inhibits digestion of soybean oil in vitro and lipid-lowering effects of digested products in cell co-culture model - Jiaying Li; Yurong Zhou; Jiayan Zhang; Ling Cui; Haina Lu; Ying Zhu; Yansheng Zhao; Songtao Fan; Xiang Xiao (Food Research International, 2023)

Seasonal Variation of Catenary-Bead Dunes in the Yangtze River Estuary: Causes and Implications - Shuwei Zheng; Xinmeng Yuan; Suxian Yang; Heqin Cheng; Xingjie Guo; Yurong Cui; Enfeng Liu; Zijun Li (Journal of Marine Science and Engineering, 2022)
Low-angle lee-side slopes of dunes are commonly developed on the world’s riverbeds, and dune migration associated with sediment transport exert a major influence on riverine processes. However, the catenary-bead dune has been identified in the Yangtze River (YR) Estuary, featuring a higher lee-side angle. To date, the morphological variation and formation reasons of catenary-bead dunes in the YR Estuary remain uncharacterized. In this study, we used a multibeam echo system (MBES) to investigate the bedforms of the YR estuary during 2014–2015, as well as to discuss the seasonal variation of catenary-bead dunes. The results indicate that the catenary-bead dunes of the YR Estuary are characterized by growth during the flood season and extinction during the dry season. The lee-side angle is typically ~16.7°, which is larger than that of other dune types (3.7–8°) in the estuary; moreover, the catenary-bead dunes are higher than other dune types of the same length in the YR Estuary. The relationship between the dune height (H) and length (L) was found to be H = 0.1667L0.603 (R2 = 0.38), while the other dune types yielded the relationship of H = 0.0845L0.758 (R2 = 0.52). Strong runoff superimposing the ebb tide led to the development of catenary-bead dunes. Furthermore, the higher coarse sediment content (69.9–72%) and lower clay content (6.3–6.7%) of the riverbed sediment are favorable for their formation, while the higher curved crest-lines are favorable for the formation of the associated elliptical pits.

Heat-air-moisture coupled model for radon migration in a porous media - Yu Cui; Shengyang Feng; Puxin Chen; Yongjun Ye; Yurong Wu; Ce Li; Rong Yang; Hong Wang (Environmental Science and Pollution Research, 2020)

Trend of the environmental supervision on submarine pipeline installation - Yurong Ouyang; Cui Wang; Yaojian Wu; Jiwei Zhang; Zhilan Lin; Ling Cai (Environmental Science and Pollution Research, 2018)

Cytotoxicity, DNA damage, and apoptosis induced by titanium dioxide nanoparticles in human non-small cell lung cancer A549 cells - Yurong Wang; Haiyan Cui; Jiaping Zhou; Fengjuan Li; Jinju Wang; Mianhua Chen; Qingdai Liu (Environmental Science and Pollution Research, 2015)

Identification of a glucose-6-phosphate isomerase involved in adaptation to salt stress of Dunaliella salina - Liuqing Cui; Yurong Chai; Jie Li; Hongtao Liu; Lei Zhang; Lexun Xue (Journal of Applied Phycology, 2010)